Tensile behaviour of adhesive anchors under different strain rates. (1st August 2019) - Ahmed, Lenda T.; Braimah, Abass
Highlights: Tensile capacity and DIF of adhesive anchors increased with increasing strain rate. Strain rate has an influence on the failure mode. Concrete cone breakout failure is observed at low strain rate. Steel anchor failure is the dominant failure mode at high strain rate. Investigate strength increase with increasing strain rate is necessary for safe design. Abstract: The use of post-installed anchors in connecting window frames to concrete elements has seen a dramatic increase in the post September-11 era. However, the behaviour of post-installed anchors under high strain rates of loading corresponding to blast loading transferred from retrofitted windows has not been extensively investigated. This paper presents the results of a finite element analysis to investigate the tensile behaviour of adhesive anchor embedded into concrete at strain rates ranging from 10 −5 s −1 to 10 3 s −1 . The adhesive anchor to concrete numerical models were validated with results from a drop-mass experimental test and then used to investigate the tensile capacity and the corresponding dynamic increase factor (DIF) at the different strain rates ( ε ̇ ) and for different anchor diameters ( d ) and embedment depths ( hef ). Failure modes and ultimate capacity under different rates of loading of the adhesive anchor were examined. The results show that the increase in the strain rate increased the tensile capacity and the DIF. The adhesive anchors exhibited maximum DIF of 3.77 under tensile load for the 19.1-mm anchor diameter with 76.2 mm embedment depth at the high strain rate of 10 3 s −1 . The strain rate affects the failure mode for the adhesive anchor; the failure mode transitions from concrete cone failure to combined cone-bond failure and then to steel failure as the strain rate increased.